1995
DOI: 10.1080/00050069508258937
|View full text |Cite
|
Sign up to set email alerts
|

Community and client perceptions of psychologists and other health professionals

Abstract: In an attempt to define Australian professional psychology's public image, a random sample of Sydney metropolitan area adults and adult clients of psychologists were surveyed to assess their knowledge of and attitudes towards mental health and physical‐health professionals. The community group held more favourable opinions of the physical‐health professionals than the mental health professionals, with psychologists generally rated quite low. The results for the clients were better but not as favourable as psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
24
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 15 publications
3
24
2
Order By: Relevance
“…Where social workers and counselling psychologists were perceived to be “very much” valued by an equal number of respondents, social workers were endorsed as “very much” needed and respected by a higher percentage of respondents than any other MHP. These outcomes are inconsistent with previous Australian findings that have implied an unfavourable public impression of psychologists (Hartwig & Delin, 2003; Hopson & Cunningham, 1995). For example, Hartwig & Delin (2003) found that psychologists were regarded by the South Australian public as the least needed professionals.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Where social workers and counselling psychologists were perceived to be “very much” valued by an equal number of respondents, social workers were endorsed as “very much” needed and respected by a higher percentage of respondents than any other MHP. These outcomes are inconsistent with previous Australian findings that have implied an unfavourable public impression of psychologists (Hartwig & Delin, 2003; Hopson & Cunningham, 1995). For example, Hartwig & Delin (2003) found that psychologists were regarded by the South Australian public as the least needed professionals.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, Hartwig & Delin (2003) found that psychologists were regarded by the South Australian public as the least needed professionals. Indeed, the present results contradict a large body of research that has shown both the public's unwillingness to seek psychological assistance (Hopson & Cunningham, 1995; Small & Gault, 1975; Thompson, Hunt, & Issakidis, 2004) and their perception of psychologists as less valuable than other professionals (Hopson & Cunningham, 1995; Sharpley, 1986). One possible explanation for this discrepancy is the presence of selection bias in the current sample, with participants recruited via a non‐random sampling strategy.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…A recent study in Australia (Hopson & Cunningham, 1995) drew upon both consumers of mental-health services (clients) and the general public (potential clients). Both groups rated seven health professions.…”
mentioning
confidence: 99%